In vitro and in vivo antileishmanial efficacy of a combination therapy of diminazene and artesunate against Leishmania donovani in BALB/c mice - Joshua Muli Mutiso; John Chege Macharia; Mustafa Barasa; Evans Taracha; Alain J. Bourdichon; Michael M. Gicheru (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
The in vitro and in vivo activity of diminazene (Dim), artesunate (Art) and combination of Dim and Art (Dim-Art) against Leishmania donovani was compared to reference drug; amphotericin B. IC50 of Dim-Art was found to be 2.28 ± 0.24 µg/mL while those of Dim and Art were 9.16 ± 0.3 µg/mL and 4.64 ± 0.48 µg/mL respectively. The IC50 for Amphot B was 0.16 ± 0.32 µg/mL against stationary-phase promastigotes. In vivo evaluation in the L. donovani BALB/c mice model indicated that treatments with the combined drug therapy at doses of 12.5 mg/kg for 28 consecutive days significantly (p < 0.001) reduced parasite burden in the spleen as compared to the single drug treatments given at the same dosages. Although parasite burden was slightly lower (p < 0.05) in the Amphot B group than in the Dim-Art treatment group, the present study demonstrates the positive advantage and the potential use of the combined therapy of Dim-Art over the constituent drugs, Dim or Art when used alone. Further evaluation is recommended to determine the most efficacious combination ratio of the two compounds.